2014
DOI: 10.1155/2014/120673
|View full text |Cite
|
Sign up to set email alerts
|

Ecto-nucleotidases Activities in the Contents of Ovarian Endometriomas: Potential Biomarkers of Endometriosis

Abstract: Endometriosis, defined as the growth of endometrial tissue outside the uterus, is a common gynecologic condition affecting millions of women worldwide. It is an inflammatory, estrogen-dependent complex disorder, with broad symptomatic variability, pelvic pain, and infertility being the main characteristics. Ovarian endometriomas are frequently developed in women with endometriosis. Late diagnosis is one of the main problems of endometriosis; thus, it is important to identify biomarkers for early diagnosis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…We had previously quantified ecto‐nucleotidase activity in the same kind of samples . We found that the ecto‐nucleotidase activity was significantly increased in the contents of ovarian endometriomas compared with simple cysts . Coinciding with these findings, we showed significantly higher levels of ENPP1 in endometriomas than in simple cysts.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…We had previously quantified ecto‐nucleotidase activity in the same kind of samples . We found that the ecto‐nucleotidase activity was significantly increased in the contents of ovarian endometriomas compared with simple cysts . Coinciding with these findings, we showed significantly higher levels of ENPP1 in endometriomas than in simple cysts.…”
Section: Discussionsupporting
confidence: 71%
“…We had previously quantified ecto‐nucleotidase activity in the same kind of samples . We found that the ecto‐nucleotidase activity was significantly increased in the contents of ovarian endometriomas compared with simple cysts .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations